Changing reasons for public private partnerships - Ronald W. McQuaid; Walter Scherrer (University of Salzburg, Department of Social Sciences and Economics, 2009)
This paper considers the micro- and macro-economic benefits and costs of Public Private Partnerships (PPPs) and some implications of implementing new international accounting standards IFRIC 12. If public sector financial costs are forced to move 'on balance sheet' then there are likely to be impacts on the use in PPPs by governments and other public bodies. This may move the basis of PPP choice towards a more 'level playing field' with other financing sources, potentially give a more realistic measure of future public commitments and liabilities and reduce incentives to use PPPs for budget enlargement. There may be a refocusing upon the potential efficiency gains of PPPs and potentially a reduction in their use, depending upon the exact interpretations of the standards and other factors
Keywords: 330